Tetrahydrocannabinol and Cannabidiol Use in an Outpatient Palliative Medicine Population. (August 2020) - Highet, Bridget H.; Lesser, Elizabeth R.; Johnson, Patrick W.; Kaur, Judith S.
Background: Palliative medicine physicians are challenged by lack of guidance regarding effectiveness and dosing of cannabis products in the setting of their emerging popularity. Objective: The aim of this study was to describe early patterns of tetrahydrocannabinol (THC) and cannabidiol (CBD) use in Florida following passage of the state's first medical marijuana law. We describe here the perceived benefits, side effects, and beliefs expressed by patients in a single outpatient academic palliative medicine practice. Methods: A cross-sectional survey was performed of a sequential convenience sample of patients who presented to an outpatient academic palliative medicine clinic over a 3-month period. Results: In all, 24% (14/58) of respondents reported THC use, with half using THC on a daily basis. Patients reported improvements in pain, appetite, and nausea. In all, 71% (10/14) began using THC after the diagnosis of their chronic illness, and the most common form of usage was vaping. In all, 24% (14/58) of patients reported CBD use. Patients reported improvements in pain, and the most common form of usage was topical application. None of the patients had used CBD prior to the onset of their chronic illness. In all, 21% (3/14) of THC users and 21% (3/14) of CBD users thought that their substance was helping to cure their illness. Individual reported side effects in both groups were minimal. Conclusions: Approximately a quarter of outpatient palliative care patients use THC or CBD, often on a daily basis. Palliative care providers should be aware of the frequency, diverse usage, and beliefs behind cannabis product use in this patient population.